Russische grammatica - Barentsen, Adriaan (University of Groningen Press, 2024)
This book is the most comprehensive Dutch-language reference work on Russian grammar. It is not primarily intended for beginners, but for users who have a decent basic knowledge of Russian. One can think of advanced students or course participants. The book is also written for users with a more than superficial interest in Russian. The topics are covered in depth and much attention is paid to making connections that help the user see the language as a coherent whole and not as a collection of separate facts. The book is basically laid out as one would expect from this genre (non-Russian-language grammars of Russian): first a chapter on writing and pronunciation, then the theory of form, broken down by word type, and the chapters covering meaning, usage and sentence structure. The Russian verb is notoriously complex, both in form and in meaning and usage. This grammar contains, after the form theory of the verb, separate chapters on meaning and usage of the various forms.